Efficacia della formazione sulla riduzione degli infortuni da lavoro: l’esperienza della linea ferroviaria ad alta velocità Torino-Novara / Effectiveness of a training programme in reducing occupational injuries: the Turin-Novara high-speed railway line experience - Bena, A.; Merchialla, P.; Coffano, et al., E. (La Medicina del Lavoro, 2009)
In letteratura vi sono poche evidenze sull’efficacia della campagna formativa volta a ridurre gli infortuni sul lavoro. Obiettivo dello studio è quello di valutare l’impatto, sulla frequenza infortunistica, della formazione svolta nei cantieri per la costruzione della linea ferroviaria Alta Velocità Torino-Novara. È utilizzato un disegno di studio prima-dopo; in base alle date di formazione, il confronto è variabile per ogni lavoratore. Si è osservata una riduzione del tasso infortunistico del 16% e del 25% rispettivamente per la formazione di base e per quella specifica. Tra i “costruttori” (= 63.5% dei formati) la riduzione è stata del 21% e del 26%. Tutti i risultati si sono dimostrati statisticamente significativi. In conclusione l’impatto della campagna formativa sugli infortuni è stato positivo. Effectiveness of a training programme in reducing occupational injuries: the Turin-Novara high-speed railway line experience Background: There is little evidence in the literature to suggest that safety training is effective in reducing injuries at the workplace. Objective: This study aimed at assessing the impact of a safety training programme on injury rates during construction work on the Turin-Novara high-speed railway line (2002-2006). Methods: We adopted a before-after study design. Since workers were enrolled and trained at different times, pre- and post-training periods were calculated individually for each worker. Results: At the end of the training programme, the incidence of occupational injuries had fallen by 16% in the case of basic training and 25% for specific training. In the construction workers group (63.5% of trained workers) the reductions were 21% for basic training and 27% for specific training. All variations were statistically significant. Conclusion: Implementation of the training programme described led to a reduction in injury rates.